Incision capsular bag herniation during subluxated lens surgery: mechanisms, management, and prevention - Ni, Shuang; Lyu, Danni; Fang, Jianxia; Xu, Wen (Frontiers in Medicine, 2025)
PurposeTo investigate the mechanism, intraoperative characteristics, management, and prevention of incision capsular bag herniation (ICBH), a previously unreported complication during cataract surgery in eyes with lens subluxation.MethodsA retrospective observational case series was conducted on five male patients who developed ICBH during phacoemulsification with intraocular lens (IOL) implantation between January 2019 and December 2024. Among 867 subluxated-lens surgeries performed during this period, the estimated incidence of ICBH was 0.58%. Clinical data was reviewed to identify predisposing factors and outcomes. Each case was managed through a stepwise intraoperative process consisting of IOP reduction, capsular decompression, capsular bag repositioning, and anterior vitrectomy.ResultsICBH occurred adjacent to the main corneal incision near areas of 1–2 quadrants of zonular dialysis. Triggers included IOL injector insertion (2 cases), ophthalmic viscosurgical device (OVD) injection (1 case), and aspiration tip withdrawal (2 cases). Contributing factors included elevated IOP and sudden decompression. The herniated tissue comprised an OVD-distended capsular bag with vitreous incarceration. The stepwise protocol led to successful capsular repositioning and in-the-bag IOL implantation in all cases. Best-corrected visual acuity improved from a preoperative range of 1.3 to 0.3 logMAR (median, 0.5) to a postoperative range of 0.7 to 0.0 logMAR (median, 0.1). No IOL decentration occurred. One case each of cystoid macular edema and choroidal detachment was noted.ConclusionICBH results from zonular weakness, incision location, IOP fluctuation, OVD dynamics, and capsular biomechanics. With appropriate intraoperative management, favorable outcomes are achievable. Prevention includes zonular assessment, incision planning, and pressure control. Further studies are needed.